Dammarane Triterpenoids from Aglaia eximia Miq. and Their Cytotoxic Activity Against P388 Murine Leukemia Cell - Farabi, Kindi; Harneti, Desi; Nurlelasari, Nurlelasari; Maharani, Rani; Mayanti, Tri; Hidayat, Ace Tatang; Fajriah, Sofa; Naini, Al Arofatus; Sofian, Ferry Ferdiansyah; Azmi, Mohamad Nurul; Supratman, Unang (Universitas Jenderal Soedirman, 2025)
ABSTRACT. Triterpenoids are a large group of secondary metabolites commonly found in plants, exhibiting high diversity in both structural features and biological activities. Meliaceae family is knows as a rich source of the triterpenoid compounds. As the most extensive genus within the Meliaceae family, Aglaia is known to contain many bioactive triterpenoid compounds, including cytotoxic triterpenoids. Among the various types of triterpenoids, dammarane is frequently found in Aglaia and has demonstrated potential cytotoxic activity. This purpose of the research was to isolate and structure determination of four dammarane triterpenoids from the methanol extract of Aglaia eximia stem bark. All four compounds were successfully isolated and identified as, dammar-24-en-3a,20-diol (1), 20S,24S-epoxy-dammar-3a,25-diol (2), (E)-dammar-23-en-3a,20,25-triol (3), and (E)-25-hydroperoxydammar-23-en-3a,20-diol (4), respectively. The compounds were analyzed using a combination of spectroscopic techniques, including HRMS (high-resolution mass spectroscopy), FTIR (fourier transform infrared spectroscopy), and NMR (nuclear magnetic resonance, one and two dimensional). Cytotoxicity assays using the MTT method were applied to compounds 1-4. All isolated compounds (1-4) generated moderate cytotoxic activity against P388 murine leukemia cells with IC50 9.09, 11.03, 5.89, and 5.74 μg/mL, respectively. Preliminary structure-activity relationship (SAR) analysis suggested that the presence of hydroxyl and hydroperoxyl groups at C-25 increases cytotoxicity, whereas the cyclization in the side chain to form an epoxide ring decreases cytotoxicity. Keyword: Triterpenoids, Meliaceae, Aglaia eximia, cytotoxicity, P388 murine leukemia cells